Quantitative fidelity of recent freshwater mollusk assemblages from the Touro Passo River, Rio Grande do Sul, Brazil - Martello,Alcemar R. (2006)
This study represents one of the first contributions to the knowledge on the quantitative fidelity of the recent freshwater molluscan assemblages in subtropical rivers. Thanatocoenoses and biocoenoses were studied in straight and meandering to braided sectors, in the middle course of the Touro Passo River, a fourth-order tributary of the Uruguay River, located in the westernmost part of the State of Rio Grande do Sul. Samplings were carried out through quadrats of 5 m², five in each sector. A total area of 50 m² was sampled. Samplings were also made in a lentic environment (abandoned meander), with intermittent communication with the Touro Passo River, aiming to record out-of-habitat shell transportation from the lentic communities to the main river channel. The results show that, despite the frequent oscillation of the water level, the biocoenosis of the Touro Passo River shows high ecological fidelity and undergoes little influence from the lentic vicinal environments. The taxonomic composition and some features of the structure of communities, especially the dominant species, also reflect some ecological differences between the two main sectors sampled, such as the complexity of habitats in the meandering-sector. Regarding the quantitative fidelity, 60% of the species found alive were also found dead and 47.3% of the species found dead were also found alive, at river-scale. However, 72% of the dead individuals belong to species also found alive. This value might be related with the good rank order correlation obtained for live/dead assemblages. Consequently, the dominant species of the thanatocoenoses could be used to infer the ecological attributes of the biocoenoses. The values of all the indexes analyzed were very variable in small-scale samplings (quadrat), but were more similar to others registered in previous studies, when they were analyzed in a station and river scale.